2022
DOI: 10.1186/s12917-022-03312-6
|View full text |Cite
|
Sign up to set email alerts
|

Salvia miltiorrhiza polysaccharides ameliorates Staphylococcus aureus-induced mastitis in rats by inhibiting activation of the NF-κB and MAPK signaling pathways

Abstract: The lactation capacity of dairy cows is critical to the productivity of the animals. Mastitis is a disease that directly affects the lactation capacity of cows. Staphylococcus aureus (S. aureus) is one of the most important pathogens that causes mastitis in dairy cows. The anti-inflammatory effect of Salvia miltiorrhiza polysaccharides (SMPs) has been demonstrated in mice and chickens. However, the effectiveness of SMPs in preventing and treating mastitis is unclear. Therefore, the purpose of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Mastitis, a disease that affects both humans and dairy herds, is recognized as the most common source of losses in the dairy industry. [43]. In addition to external pathogens infecting the mammary gland, an increasing number of studies in recent years have shown that the gut microbiota plays a crucial role in the pathogenesis of mastitis [40] [2].…”
Section: Discussionmentioning
confidence: 99%
“…Mastitis, a disease that affects both humans and dairy herds, is recognized as the most common source of losses in the dairy industry. [43]. In addition to external pathogens infecting the mammary gland, an increasing number of studies in recent years have shown that the gut microbiota plays a crucial role in the pathogenesis of mastitis [40] [2].…”
Section: Discussionmentioning
confidence: 99%
“…Mastitis is an inflammatory response caused by breast tissue infections, which can be caused by a variety of bacteria [ 85 ]. And S. aureus is one of the most common pathogens of bovine infectious mastitis, as well as intramammary infections of dairy goats, which is widespread in many countries, seriously restricting the development of the global dairy industry [ 86 , 87 , 88 ].…”
Section: Mastitismentioning
confidence: 99%
“…It was found that organic selenium might regulate the inflammatory response by suppressing the activation of the NF-κB signaling pathway and attenuating the inflammatory reaction to infections by modulating the MAPK signaling pathway. Zhang et al’s study found that the anti-inflammatory effect of salvia miltiorrhizae polysaccharides (SMPs) on mastitis induced by S. aureus in rats might be related to the inhibition of the activation of NF-κB and MAPK signaling pathways and thus the inhibition of the expression of inflammatory cytokine genes [ 85 ].…”
Section: Mastitismentioning
confidence: 99%
See 1 more Smart Citation